Recent Advances in Wide-Bandgap Organic–Inorganic Halide Perovskite Solar Cells and Tandem Application - Nie, Ting; Fang, Zhimin; Ren, Xiaodong; Duan, Yuwei; Liu, Shengzhong (Frank) (Nano-Micro Letters, 2023)
Perovskite-based tandem solar cells have attracted increasing interest because of its great potential to surpass the Shockley–Queisser limit set for single-junction solar cells. In the tandem architectures, the wide-bandgap (WBG) perovskites act as the front absorber to offer higher open-circuit voltage (VOC) for reduced thermalization losses. Taking advantage of tunable bandgap of the perovskite materials, the WBG perovskites can be easily obtained by substituting halide iodine with bromine, and substituting organic ions FA and MA with Cs. To date, the most concerned issues for the WBG perovskite solar cells (PSCs) are huge VOC deficit and severe photo-induced phase separation. Reducing VOC loss and improving photostability of the WBG PSCs are crucial for further efficiency breakthrough. Recently, scientists have made great efforts to overcome these key issues with tremendous progresses. In this review, we first summarize the recent progress of WBG perovskites from the aspects of compositions, additives, charge transport layers, interfaces and preparation methods. The key factors affecting efficiency and stability are then carefully discussed, which would provide decent guidance to develop highly efficient and stable WBG PSCs for tandem application. Highlights: 1 Wide-bandgap perovskite solar cells are reviewed in detail from the views of compositions, additives, charge transport layers, interfaces and preparation methods. 2 The key factors affecting open-circuit voltage and photostability are carefully discussed. 3 The future directions and challenges in developing wide-bandgap perovskite solar cells are highlighted.